BLENDED TEACHING FOR RESEARCH METHODS AND STATISTICS COURSES - Zhou, Yuchun (PEOPLE: International Journal of Social Sciences, 2018)
A solid understanding of statistics and research methods is essential for all graduate students in education, social sciences, and psychology. However, effective teaching in statistics and research methods is challenging because students are less likely to enjoy these courses. The author of this paper argued that blended teaching should work as an alternative to traditional face-to-face teaching, including (1) conceptual lectures in class and hands-on activities out of class, (2) lab work online by group with peer support, (3) project-based course design. At the end of this paper, instructor’s self-reflection and students’ feedback on blended teaching were reported. This paper is of interest to both faculty and students who are teaching and learning statistics.